Therapists as agents of social control: a grounded theory of ethical and practical implications - Lechtenberg, Marcie Marie (Kansas State University, 2014)
This dissertation presents an emerging inquiry about family therapists’ lived experiences as they work with families in situations that may also require the therapist to act as agents of social control whether through implementation of therapy, treatment, or programs. I used a grounded theory approach, informed by feminist qualitative research, to address the following three questions: 1) How do therapists experience their role as agents of social control? 2) What processes and strategies do they use as they navigate that role when working from a social justice perspective and 3) what implications does this have for family therapists as they conceptualize and plan treatment for their cases? This study used purposeful sampling: Eleven professional family therapists who have researched, taught and written about social justice issues were interviewed. The results of this study provide a preliminary map clarifying how family therapists navigate that role of working as an agent of social control while maintaining a social justice perspective. This research clarifies family therapists’ recognition of their role as agents of social control through the context, meaning, and expectations of therapy. The navigation of this role from a social justice perspective is accomplished through the therapists’ framework of therapy, their understanding of the lived experiences of their client systems, and their therapeutic approach to therapy. These participants also addressed the supervision and development of beginning therapists. These results are intended to provide a foundation for further discussion and research on the topic of therapists as agents of social control.
Keywords: Therapists; Social justice; Social control; Psychology (0621)